2020
DOI: 10.32861/ijefr.67.192.200
|View full text |Cite
|
Sign up to set email alerts
|

Internal Factors Influencing the Profitability of Commercial Banks in Bangladesh

Abstract: The profitability of commercial banks is influenced by a number of internal and external factors. This paper attempts to identify the internal factors which significantly influence the profitability of commercial banks in Bangladesh. In this study, profitability is measured by ROA and ROE which may be significantly influenced by the internal factors such as IRS, NIM, CAR, CR, DG, LD, CTI and SIZE of the bank. Data are collected from published annual reports during 2014--2018 of 23 commercial banks. Using simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…LQR, which is metric for meeting short-term obligations from banks' liquid assets, showed the positive but negligible effect on ROA with value of 0.3617 indicating that liquidity has inconsequential effect on profitability. This result corroborates the findings of Nguyen (2022), Koroleva (2021) and Hosen, (2020). Moreover, ROA was significantly but unfavorably impacted by NPLR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…LQR, which is metric for meeting short-term obligations from banks' liquid assets, showed the positive but negligible effect on ROA with value of 0.3617 indicating that liquidity has inconsequential effect on profitability. This result corroborates the findings of Nguyen (2022), Koroleva (2021) and Hosen, (2020). Moreover, ROA was significantly but unfavorably impacted by NPLR.…”
Section: Discussionsupporting
confidence: 91%
“…The negative sign, denotes an unexpected rise in interest rates, deters bank customers from taking out loans, raises borrowers' interest payments, lowers repayment capacity, raises default rate and lowers banks' profitability respectively. This report is in tandem with Hosen (2020).…”
Section: Discussionsupporting
confidence: 78%
“…He came to the conclusion that the loan portfolio has a significant negative impact on the profitability of the bank. Hosen ( 2020 ) investigated 23 commercial banks in Bangladesh and discovered that interest rate spread, capital adequacy, and liquidity are all important factors. Lestaria et al ( 2021 ) discovered that liquidity and leverage have a negative impact on the profitability (ROE), whereas the bank size has a positive impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their study, they showed that highly skilled banks can produce more profit than less competent one; loan growth and diversification affect positively on profitability and funding cost affect negatively to generate profit. Hosen (2020) performed a study in Bangladesh on 23 commercial banks and found that banks' specific factors like interest rate spread, capital adequacy ratio, credit risk, deposit growth, loan to deposit ratio, cost to income ratio and size of the bank significantly affect profitability of banks measured in terms of ROA and ROE. Flamini et al (2009) and Athanasoglou et al (2006) employed bank specific factors like operating expenses, asset quality, management efficiency, bank size, capital Islam / International Journal of Finance &Banking Studies, Vol 10 No 2, 2021 ISSN: 2147-4486 Peer-reviewed Academic Journal published by SSBFNET with respect to copyright holders.…”
Section: Literature Reviewmentioning
confidence: 99%